Fungal infections in patients after recovering from COVID-19: a systematic review - Ulloque-Badaracco, Juan R. (2024)
Background and aims: The presence of fungal infections has been described in patients after recovering from COVID-19. This study aims to conduct a systematic review of studies that reported fungal infections (Mucor spp., Pneumocystis jirovecii, or Aspergillus spp.) in adults after recovering from COVID-19. Methods: We performed a systematic review through PubMed, Web of Science, OVID-Medline, Embase, and Scopus. The study selection process was performed independently and by at least two authors. We performed a risk of bias assessment using the Newcastle–Ottawa Scale for cohort and case–control studies, and the Joanna Briggs Institute’s Checklists for Case Series and Case Reports. Results: The systematic search found 33 studies meeting all inclusion criteria. There was a total population of 774 participants, ranging from 21 to 87 years. From them, 746 developed a fungal infection. In 19 studies, Mucor spp. was reported as the main mycosis. In 10 studies, P. jirovecii was reported as the main mycosis. In seven studies, Aspergillus spp. was reported as the main mycosis. Regarding the quality assessment, 12 studies were classified as low risk of bias and the remaining studies as high risk of bias. Conclusion: Patients’ clinical presentation and prognosis after recovering from COVID-19 with fungal infection differ from those reported patients with acute COVID-19 infection and those without COVID-19 infection.